The effects of rules on local political decision-making processes: How can rules facilitate participation? - Insa Theesfeld; Tom Dufhues; Gertrud Buchenrieder (Policy Sciences, 2017)
It is often claimed that participation empowers local actors and that an inclusive decision-making process is crucial for rural development. We aim to investigate how formal and informal rules are set in local decision-making processes and how those rules may impact the actual level of participation by local actors. In a comparative case study, the rules-in-use for the planning of community projects in Thailand are examined. For our analysis, we use the Institutional Analysis and Development framework, which allows for more precise analysis of the impact of the rules. Fifty-three villages are served by four selected Tambon Administrative Organisations (TAO) which are either known for success in achieving participation or ranked as problematic in implementing the decentralization and local participation goals of the Thai government. The study is based on 60 semi-structured interviews with TAO staff, a survey of village leaders in 50 villages and a household survey of 104 villagers. We scrutinize seven types of rules and show some particular differences in terms of the impact from the rules-in-use. In the TAOs ranked as less participatory, the attendance rate in the meetings is found to be lower (boundary rule), villagers are informed about a meeting with a shorter notice (information rule) and more villagers mention that elites interfere in the project selection process (aggregation rule). A high level of fuzziness appeared in the position and authority rules. Further, we obtained information on the particular deontic logic, showing generally a high share of de facto may-statements in the implementation of the rules. We conclude that if the policy goal is enhancing participation, rule-setting offers good scope for intervention. From a practical perspective, information on administrative procedures has to be made more accessible and public administrators should receive procedural training.
Keywords: 330; political decision-making; participation; rules; IAD framework; deontic logic; Thailand